Pengaruh Literasi Keuangan Syariah dan Citra Bank terhadap Keputusan Nasabah dalam Menggunakan Produk Pembiayaan KPR di Bank Tabungan Negara KC Syariah Palembang - Pina Wahana; Zuul Fitriani Umari; Pamuji Pamuji (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the influence of Islamic financial literacy and bank image on customer decisions in using mortgage financing products at Bank Tabungan Negara (BTN) KC Syariah Palembang. Islamic financial literacy plays an important role in increasing public understanding of Islamic banking products, which will influence decisions in choosing financial products. In addition, a positive bank image also contributes to building customer trust in the services offered. This study uses a quantitative method with the Structural Equation Modeling-Partial Least Squares (SEM-PLS) approach. Data were collected by distributing questionnaires to BTN KC Syariah Palembang customers who use mortgage financing products. The results of the study indicate that Islamic financial literacy and bank image have a positive and significant effect on customer decisions. The implications of this study indicate that increasing Islamic financial literacy and strengthening bank image can be an effective strategy for Islamic banks in increasing the number of users of Islamic-based mortgage products. Therefore, a broader Islamic financial education program is needed as well as improving the quality of services and transparency in Islamic banking operations to build customer trust and loyalty..